Parents' Empathic Accuracy: Associations With Type 1 Diabetes Management and Familism. (1st August 2021) - Main, Alexandra; Kho, Carmen; Miramontes, Maritza; Wiebe, Deborah J; Çakan, Nedim; Raymond, Jennifer K
Abstract: Objective: To (1) test associations between parents' empathic accuracy for their adolescents' positive and negative emotions and adolescents' physical and mental health (HbA1c, diabetes self-care, and depressive symptoms) in a predominantly Latinx sample of adolescents with type 1 diabetes and their parents, and (2) explore how familism values were associated with parent empathic accuracy and adolescent physical and mental health in this population. Methods: Parents and adolescents engaged in a discussion about a topic of frequent conflict related to the adolescents' diabetes management. Parents and adolescents subsequently completed a video recall task in which they rated their own and their partner's emotions once per minute; parents' empathic accuracy was calculated from an average discrepancy between parent and adolescent ratings of the adolescent's emotions. Adolescents reported on their depressive symptoms and both parents and adolescents reported on adolescents' diabetes self-care and their own familism values; HbA1c was obtained from medical records. Results: Results from structural equation modeling revealed that parents' empathic accuracy for adolescents' negative (but not positive) emotions was uniquely associated with adolescents' HbA1c, self-care, and depressive symptoms. There was limited evidence that familism was related to parent empathic accuracy or adolescent physical and mental health. Conclusions: Promoting parents' empathic accuracy for adolescents' negative emotions in the context of type 1 diabetes management may have important implications for adolescents' mental and physical health.